Study the Effect of Doping and Thickness on I-V characteristic of Silicon Solar Cells Using PC1D Simulation - Yadgar Hussein Shwan; Berun Nasralddin Ghafoor (Tikrit Journal of Pure Science)
Energy from renewable sources has developed significantly in the past few decades. Photovoltaics have played a crucial role in the technology employed to generate this type of energy. Technicians and researchers can benefit from systems that offer knowledge and data on the efficiency and performance of solar cells. In this work the I-V characteristic of photovoltaic of silicon was measured, and the influence of different n-type thicknesses was examined with their different doping concentration; this has been done by PC1D simulation, It would be appropriate for developing silicon single-layer without cost. The n-layer thickness and n-region doping are the factors responsible for a solar cell's efficiency and performance. In this context silicon is the ideal candidate due to the swift increase in their efficiency, and its dependability and stability. In the end, to draw a conclusion around the ideal parameters that a good solar cell has to have, the optimum external quantum efficiencies obtained from this design were (87.71 %) for mono layer front surfaces. The results from these simulation studies prove that it is possible to propose these design parameters for mono layer solar cell fabrication. By adjusting the effectively mentioned parameters, a great efficient and I-V characteristic solar cell has been achieved.